FISH SPECIES COMPOSITION AND DIVERSITY OF DADIN-KOWA RESERVOIR GOMBE STATE, NIGERIA - R, YERIMA; S, NAZEEF; U, BAYERO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Climatic characteristics affect water quality and quantity and this inevitably affects biodiversity. The study was conducted for eight months to determine the composition and diversity of fish species in Dadin Kowa Reservoir. Fish samples were taken at three stations using conventional fishing gear. The fish samples were identified using standard description keys. The Shannon Weiner Diversity Index was used to determine the diversity of fish species in the reservoir. A one-way analysis of variance (ANOVA) was used to test for significant monthly variations in fish species, and Duncan's multiple range test (DMRT) was used to separate the means where significant differences existed. Thirty (30) fish species belonging to eleven (11) families were identified from a total of 690 fish samples. The Mormyridae family had the most species (6), followed by the Mochokidae family (5), then the Alestidae, Cyprinidae, Clariidae, and Claroteidae families, while the Malapteruridae, Polypteridae, and Schilbeidae families had one species each. The Mormyridae family had the highest proportion of species with 20.0% fish, followed by Mochokidae with 16.7%. The families Malapteruridae, Polypteridae and Schilbeidae had the lowest catches with 3.3%. The genus Petrocephalus had the highest proportion of fish with 18.99%, followed by Heterobranchus with 16.23%. The genus Malapterurus was the least caught with 0.72% fish. Of the total fish species examined, Mormyrops anguilloides, Clarias anguillaris, and Schilbe mystus had 14.5%, 8.7%, and 8.6% of the fish composition, respectively. Labeo senegalensis and Synodontis budgetti had 6.9% and 5.8%, respectively. While the remaining fish species had a percentage occurrence of less than 5%. There was significant variation (P ≤ 0.05) in the number of fish species sampled monthly in the reservoir. The highest diversity index of 2,056 was found in the family Cyprinidae. The lowest index value of 1.32 was obtained in the family Claroteidae. The level of family uniformity was lowest in the Alestidae (0.83) and highest in the Cyprinidae (0.98). The genera Hyperopisus, Mormyrops, and Malapterurus had the lowest indices, while Petrocephalus, Clarias, Barbus, and Oreochromis had the most fish species. The study revealed a rich fish composition with important economic species and a highly diversified fish community structure in the reservoir